Approaching Elaborate Control of the Nano‐Products of Carbothermal Reduction Reaction Through In Situ Identification. Issue 15 (6th January 2023) - Zhang, Jialin; Ji, Yuan; Liu, Huating; Cheng, Ningyan; Guo, Siqi; Yang, Ming; Ren, Long; Ge, Binghui
Abstract: Atomic understanding of a chemical reaction can realize the programmable design and synthesis of desired products with specific compositions and structures. Through directly monitoring the phase transition and tracking the dynamic evolution of atoms in a chemical reaction, in situ transmission electron microscopy (TEM) techniques offer the feasibility of revealing the reaction kinetics at the atomic level. Nevertheless, such investigation is quite challenging, especially for reactions involving multi‐phase and complex interfaces, such as the widely adopted carbothermal reduction (CTR) reactions. Herein, in‐situ TEM is applied to monitor the CTR of Co3 O4 nanocubes on reduced graphene oxide nanosheets. Together with the first‐principle calculation, the migration route of Co atoms during the phase transition of the CTR reaction is revealed. Meanwhile, the interfacial edge‐dislocations/stress‐gradient is identified as a result of the atomistic diffusion, which in turn can affect the morphology variation of the reactants. Accordingly, controllable synthesis of Co‐based nanostructure with a desirable phase and structure has been achieved. This work not only provides atomic kinetic insight into CTR reactions but also offers a novel strategy for the design and synthesis of functional nanostructures for emerging energy technologies. Abstract : Present study pioneers an in‐depth understanding of the dynamic phase and structure evolution during carbothermal reduction (CTR) reaction by using in situ transmission electron microscopy (TEM) technology. The atomic kinetic insights including the migration route of atoms and possible stress‐gradient are clarified, which offers a novel strategy for controllably producing nanostructures with complex composition and desired structure.